ANALISIS IMPLEMENTASI BUDAYA 5S DALAM PENATAAN LABORATORIUM TEKNIK INDUSTRI UNIVERSITAS HASYIM ASY’ARI - Ardi Setiawan; Sulung Rahmawan Wira Ghani (INVANTRI (Inovasi Dan Pengelolaan Industri), 2023)
Industrial engineering is an engineering field that includes the knowledge of design, repair, and manufacture integrated systems consisting of people, raw materials, information, equipment, and energy. The laboratory is used to complete the observed research, especially industrial problems in the industrial engineering department. Based on previous research, as many as 62.5% of lecturers found it difficult to store laboratory equipment in the workspace and 81.25% suggested to rearrange the layout of the laboratory. This study aimed to design the layout of laboratory equipment by using the 5S method. The first step to do the research was reducing laboratory activities, initial identifying of laboratory layouts, grouping the machines and tools, designing the laboratory layouts, implementing 5S, and evaluating new designs by using the Self-Assessment Form. The resulting layout is in accordance with the 5S principle, the design of the wardrobe is relatively small, and the design adapts to the space and equipment stored. The results then showed that 5S performance data in the laboratory before the implementation was 0.71 which in the fair rating category, and after the application of 5S the average score becomes 1.5 which in the excellent rating category. However, it shows that there is two-fold increase before the implementation 5S method.